Sustainable environmental geotechnics practices for a green economy - O'Kelly, Brendan (My University, 2022)
The revitalisation of the global economy after the Covid-19 era presents environmental geotechnics with the opportunity to reinforce the need for a change in paradigm towards a green, circular economy and to promote aggressively the use and development of sustainable technologies and management practices. This paper aims to assist in this effort by concentrating on several thematic areas where sustainability solutions and future improvements are sought. These include the re-entry of construction and demolition of wastes, excavated materials, industrial wastes and marine sediments into the production cycle and the reuse of existing foundations. Despite the recent trend in advanced countries towards recycling and waste-to-energy thermal treatment, landfills still constitute the most common municipal solid waste management practice, especially in low-and-middle-income countries, and technological solutions to improve their environmental footprint are hereby presented. At the same time, remediation solutions are required to address the multitude of contaminated sites worldwide. Advanced developments that incorporate environmental, economic and social dimensions are expounded by the authors, together with sustainable ground improvement solutions for infrastructure projects conducted in soft and weak soils. The topic of thermo-active geostructures concludes this paper, where, apart from their infrastructure utility, these structures have the potential to contribute to the renewable energy source.
PUBLISHED
Winner of the Environmental Geotechnics Prize at the ICE Publishing Annual Awards 2023 (prize presented to the best paper published in the Journal of Environmental Geotechnics for the year 2022)
Keywords: Rehabilitation; Reclamation & renovation/renewable energy/waste management & disposal; International Development; Smart & Sustainable Planet; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; Geothermal Energy; Green Infrastructure; Ground improvement; Hazardous Wastes; Industrial Waste; MARINE SEDIMENTS; RECENT MARINE-SEDIMENTS; Renewable Energy Sources; Renewable energy; SOIL CONTAMINATION; SOIL MODIFICATION; SUSTAINABLE DEVELOPMENT; Soil Mechanics; Soil Mechanics & Foundations; Soil remediation; Solid Waste Disposal; Waste tires; geostructures; geotechnical; landfilling; sustainable construction; waste tyres